Heavy steel plate and its manufacturing method

A specific composition and manufacturing process for thick steel plates, including controlled hot rolling and cooling, address the insufficient fatigue limit ratio issue, resulting in improved fatigue resistance and cost-effectiveness.

JP7620460B2Active Publication Date: 2025-01-23KOBE STEEL LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2021048989
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-06-30
Filing Date
2021-03-23
Publication Date
2025-01-23
Estimated Expiration
2041-03-23

AI Technical Summary

Technical Problem

Conventional thick steel plates do not achieve a sufficiently high fatigue limit ratio, which is crucial for large structures like ships, buildings, and bridges, leading to potential fatigue failures and increased manufacturing costs due to the use of high-strength materials.

Method used

A thick steel plate composition with specific element ratios (C, Si, Mn, P, S, Cu, Al, Nb, Ti, N, and others) and a controlled metal structure (MA fraction and low-angle grain boundaries) is combined with a manufacturing process involving hot rolling in a two-phase temperature range and controlled cooling to achieve a high fatigue limit ratio.

Benefits of technology

The solution results in a thick steel plate with a significantly improved fatigue limit ratio, enhancing structural reliability and reducing manufacturing costs by utilizing standard materials effectively.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007620460000009
    Figure 0007620460000009
  • Figure 0007620460000010
    Figure 0007620460000010
  • Figure 0007620460000011
    Figure 0007620460000011
Patent Text Reader

Abstract

To provide a thick steel plate having a sufficiently high fatigue limit ratio, and a method for manufacturing the same.SOLUTION: A thick steel plate has a component composition comprising 0.02-0.10 mass% C, 0.10-0.60 mass% Si, 1.00-2.00 mass% Mn, more than 0 mass% but 0.035 mass% or less P, more than 0 mass% but 0.035 mass% or less S, 0.10-0.60 mass% Cu, 0.010-0.060 mass% Al, more than 0 mass% but 0.050 mass% or less Nb, more than 0 mass% but 0.050 mass% or less Ti, 0.0010-0.0100 mass% N, and the balance iron with inevitable impurities, in which the total content of Si and Cu is 0.30 mass% or more, and a metallic structure has MA fraction of 0.5 area% or less and the total length of a small-angle angle grain boundary observed in a 200 μm square region satisfying 2.5 mm or more.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to steel plates and methods for making same. [Background technology]

[0002] Thick steel plates are mainly used as structural materials for ships, buildings, bridges, construction machinery, etc. Large structures such as ships, buildings, bridges, and construction machinery are becoming larger, but due to the magnitude of damage that would occur if they were to break, greater reliability is required of their structural components. It has long been known that most breaks in large structures are caused by fatigue failure, and various fatigue failure resistance technologies have been developed, but even today there are many cases where fatigue failure has led to failure.

[0003] In general, in areas of large structures where fatigue damage is likely to occur, fatigue failure has been prevented by taking measures such as changing the shape to one that is less prone to stress concentration or by using high-strength thick steel plates. However, such structures increase manufacturing costs due to additional labor and / or the use of more expensive thick steel plates. For this reason, technology is needed to improve the fatigue properties of the steel plates themselves. It is generally known that the fatigue limit of thick steel plates is proportional to tensile strength, and thick steel plates with a higher fatigue limit than this proportional relationship (i.e., thick steel plates with a high fatigue limit ratio, calculated by dividing the fatigue limit by the tensile strength) can be said to have excellent fatigue properties.

[0004] In recent years, interest in improving fatigue properties has been growing from the viewpoint of increasing design freedom for large container ships, and the Nippon Kaiji Kyokai (ClassNK) is also moving to establish rules for the method of guaranteeing the fatigue properties of steel materials. As a result, there is a demand for thick steel plates with higher fatigue limit ratios.

[0005] Patent Document 1 discloses a steel plate having excellent fatigue properties that satisfies a predetermined chemical composition and is produced under predetermined conditions, such as a finish rolling end temperature being equal to or higher than the Ar3 transformation point. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2016-855 A Summary of the Invention [Problem to be solved by the invention]

[0007] However, it has been found that in the conventional technology disclosed in Patent Document 1, the fatigue limit ratio may be insufficient.

[0008] The present invention has been made in view of the above circumstances, and one of its objects is to provide a thick steel plate having a sufficiently high fatigue limit ratio and a manufacturing method thereof. [Means for solving the problem]

[0009] Aspect 1 of the present invention is The composition of the components is C: 0.02~0.10% by mass, Si: 0.10~0.60% by mass, Mn: 1.00~2.00% by mass, P: more than 0% by mass and 0.035% by mass or less, S: more than 0% by mass and 0.035% by mass or less, Cu: 0.10~0.60% by mass, Al: 0.010~0.060% by mass, Nb: more than 0% by mass and 0.050% by mass or less, Ti: more than 0 mass% and 0.050 mass% or less, N: 0.0010 to 0.0100 mass%, and The balance is composed of iron and inevitable impurities, and The total content of Si and Cu is 0.30 mass% or more, The metal structure is MA fraction is 0.5 area% or less, and The total length of low-angle grain boundaries observed in an area of ​​200 μm square is 2.5 mm or more. It is a thick steel plate that satisfies the above requirements.

[0010] Aspect 2 of the present invention is Ni: more than 0% by mass and not more than 1.00% by mass, Ca: more than 0% by mass and 0.0050% by mass or less, B: More than 0.0003 mass% and 0.0050 mass% or less, V:0.003~0.500% by mass, Cr: 0.05 to 1.00 mass%; and The steel plate according to embodiment 1, further comprising one or more elements selected from the group consisting of 0.010% by mass or more and less than 0.05% by mass of Mo.

[0011] Aspect 3 of the present invention is REM: More than 0% by mass and 0.0060% by mass or less, Zr: more than 0% by mass and 0.0050% by mass or less, Mg: 0.0005 to 0.0100% by mass, and The steel plate according to aspect 1 or 2, further containing one or more selected from the group consisting of Ta: 0.010 to 0.500 mass %.

[0012] A fourth aspect of the present invention is The steel plate according to any one of Aspects 1 to 3, wherein a hardenability index DI2 represented by the following formula (1) is 3.90 or less: DI2 = 1.16 × (0.77 / 10) 0.5 ×(0.7×[Si]+1)×(5.1×([Mn]-1.2)+5)×(0.35×[Cu]+1)×(0.36×[Ni]+1)×(2.16×[Cr]+1)×(3×[Mo]+1)×(1.75×[V]+1)×(400×[B * ]+1) ···(1) In formula (1), [Si], [Mn], [Cu], [Ni], [Cr], [Mo] and [V] represent the contents of Si, Mn, Cu, Ni, Cr, Mo and V, respectively, expressed in mass%, and [B * ] is the effective amount of dissolved B, which is expressed by the following formula (2). [B *]=[B]-(([N]-[Ti]×14 / 48)×11 / 14) ···(2) In formula (2), [B], [N] and [Ti] respectively represent the contents of B, N and Ti expressed in mass%. * ]<4×10 -4 (mass%), [B * ]=0 (mass%).

[0013] A fifth aspect of the present invention is A step of preparing a steel slab having a composition according to any one of aspects 1 to 4; hot rolling the slab at a rolling reduction of 10% or more in a two-phase temperature range; The method for producing the steel plate according to any one of Aspects 1 to 4 includes, after the step of hot rolling in the two-phase temperature region, a step of cooling to room temperature at an average cooling rate of 3° C. / sec or less.

[0014] A sixth aspect of the present invention is After the step of preparing the steel slab, and before the step of hot rolling in the two-phase temperature range, a step of heating the steel slab to 1000 to 1250°C; The method according to aspect 5, further comprising, after the heating step, performing hot rolling in a non-recrystallized region with a rolling reduction of 10% or more. Effect of the Invention

[0015] According to the embodiments of the present invention, it is possible to provide a thick steel plate having a sufficiently high fatigue limit ratio and a manufacturing method thereof. [Brief description of the drawings]

[0016] [Figure 1] FIG. 1 shows top views of tensile test pieces of the examples and comparative examples. [Figure 2A] FIG. 2A shows top views of fatigue test pieces of Examples 1 to 7 and Comparative Examples 1 to 8. [Figure 2B] FIG. 2B shows a side view of the fatigue test pieces of Examples 1 to 7 and Comparative Examples 1 to 8. [Figure 3A] FIG. 3A shows a top view of the fatigue test specimen of Example 8. [Figure 3B] FIG. 3B shows a side view of the fatigue test specimen of Example 8. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] The present inventors have conducted research from various angles in order to realize a thick steel plate having a sufficiently high fatigue limit ratio.

[0018] As a result, it was found that by appropriately adjusting a specified component composition, reducing the fraction of a mixed phase of martensite and austenite (also referred to as island martensite, mainly referred to as "MA" in this specification) (MA fraction), and making the total length of the boundary where the orientation difference between adjacent crystal grains is 2 to 15° (hereinafter referred to as "low-angle grain boundaries") greater than or equal to a specified value, it is possible to realize a thick steel plate with a sufficiently high fatigue limit ratio. The inventors also found that controlling the hardenability index DI2 value to a predetermined value or less is a method for reducing the MA fraction. Furthermore, while in the conventional technology, hot rolling is terminated at or above the Ar3 transformation point in order to provide steel plates with excellent fatigue properties, the inventors have found, as a result of their investigations, that in order to make the total length of low-angle grain boundaries a predetermined value or more, it is necessary to set the rolling reduction in the two-phase temperature range below the Ar3 transformation point to a predetermined value or more.

[0019] The following provides details of each requirement stipulated by the embodiment of the present invention.

[0020] <1. Ingredient composition> A steel plate according to an embodiment of the present invention preferably contains C: 0.02 to 0.10 mass%, Si: 0.10 to 0.60 mass%, Mn: 1.00 to 2.00 mass%, P: more than 0 mass% and not more than 0.035 mass%, S: more than 0 mass% and not more than 0.035 mass%, Cu: 0.10 to 0.60 mass%, Al: 0.010 to 0.060 mass%, Nb: more than 0 mass% and not more than 0.050 mass%, Ti: more than 0 mass% and not more than 0.050 mass%, and N: 0.0010 to 0.0100 mass%, with the total content of Si and Cu being 0.30 mass% or more, and the balance being iron and unavoidable impurities. Each element will be described in detail below.

[0021] (C:0.02~0.10% by mass) C is an important element for ensuring the strength and fatigue properties of the base material (i.e., steel plate). Therefore, the C content is set to 0.02 mass% or more. It is preferably 0.03 mass% or more, and more preferably 0.04 mass% or more. On the other hand, if the C content is excessive, not only will the strength be too high to obtain the desired tensile strength, but the hardenability will be excessive, and when accelerated cooling is used, the MA fraction will increase, resulting in a decrease in the fatigue limit ratio. Therefore, the C content is set to 0.10 mass% or less. It is preferably 0.08 mass% or less, and more preferably 0.06 mass% or less.

[0022] (Si:0.10~0.60% by mass) Si is an element that is necessary for ensuring the strength of the base material due to its large solid solution hardening, and is also an element that is effective in extending the crack initiation life and improving the fatigue limit ratio by suppressing the proliferation of dislocations. In order to effectively exert this effect, the Si content is set to 0.10 mass% or more. It is preferably 0.20 mass% or more, more preferably 0.30 mass% or more, and even more preferably 0.35 mass% or more. However, if the Si content is excessive, there is a risk of reducing other properties such as toughness. Therefore, the Si content needs to be 0.60 mass% or less. It is preferably 0.55 mass% or less, more preferably 0.50 mass% or less, and even more preferably 0.45 mass% or less.

[0023] (Mn:1.00~2.00% by mass) Mn is an important element for ensuring hardenability in order to obtain a fine structure. To effectively exert this effect, the Mn content is set to 1.00 mass% or more. It is preferably 1.20 mass% or more, more preferably 1.40 mass% or more, and even more preferably 1.45 mass% or more. However, if the Mn content is excessive, the hardenability becomes excessive and the MA fraction increases, and sufficient fatigue properties cannot be obtained. Therefore, the Mn content is set to 2.00 mass% or less. It is preferably 1.80 mass% or less, more preferably 1.70 mass% or less, and even more preferably 1.60 mass% or less.

[0024] (P: more than 0 mass% and 0.035 mass% or less) P (phosphorus) is an element that is inevitably contained as an impurity during the manufacturing process, etc., and has a negative effect on toughness and fatigue properties, so the P content is set to 0.035 mass% or less. The less P, the better, with 0.020 mass% or less being preferred, 0.015 mass% or less being more preferred, and 0.010 mass% or less being most preferred. Note that from the viewpoint of steelmaking capacity, P may usually be contained in an amount of more than 0 mass%.

[0025] (S: more than 0% by mass and 0.035% by mass or less) Like P, S (sulfur) is an element that is inevitably contained as an impurity during the manufacturing process and has a negative effect on toughness, so the S content is set to 0.035 mass% or less. The less S there is, the better, and for example, 0.020 mass% or less is preferable, 0.015 mass% or less is more preferable, and 0.010 mass% or less is even more preferable, but it is usually contained in an amount exceeding 0 mass%, and may even be about 0.002 mass%.

[0026] (Cu:0.10~0.60% by mass) Like Si, Cu is an effective element for suppressing the proliferation of dislocations, thereby extending the crack initiation life and improving the fatigue limit ratio. In order to effectively exert this effect, the Cu content is set to 0.10 mass% or more. It is preferably 0.15 mass% or more, more preferably 0.20 mass% or more, and even more preferably 0.25 mass% or more. However, if the Cu content is excessive, not only will the hardenability become excessive, but cracks and the like will easily occur during hot working, so the Cu content is set to 0.60 mass% or less. It is preferably 0.55 mass% or less, more preferably 0.50 mass% or less, even more preferably 0.40 mass% or less, and even more preferably 0.30 mass% or less.

[0027] (Al:0.010~0.060% by mass) Al is a useful element for deoxidization, and in order to exert its effect, the Al content is set to 0.010 mass% or more. It is preferably 0.015 mass% or more, more preferably 0.020 mass% or more, and even more preferably 0.025 mass% or more. However, if the Al content is excessive, the hardenability becomes excessive, and the MA fraction increases, making it impossible to obtain the desired fatigue properties. Therefore, the Al content needs to be set to 0.060 mass% or less. It is preferably 0.050 mass% or less, and more preferably 0.040 mass% or less.

[0028] (Nb: more than 0 mass% and 0.050 mass% or less) Nb is an effective element for improving hardenability and refining the structure. To effectively exert these effects, the Nb content is set to more than 0 mass%. It is preferably 0.010 mass% or more, and more preferably 0.015 mass% or more. However, if the Nb content is excessive, the hardenability becomes excessive and the MA fraction increases, so that the desired fatigue properties cannot be obtained. Therefore, the Nb content is set to 0.050 mass% or less. It is preferably 0.040 mass% or less, more preferably 0.030 mass% or less, and even more preferably 0.025 mass% or less.

[0029] (Ti: more than 0 mass% and 0.050 mass% or less) Ti is an element that is useful for improving hardenability and at the same time forming TiN to make the structure of the heat-affected zone during welding fine, thereby suppressing a decrease in toughness. For this reason, the Ti content is set to more than 0 mass%. It is preferably 0.005 mass% or more, more preferably 0.007 mass% or more, and even more preferably 0.010 mass% or more. However, if the Ti content is excessive, coarse TiN may be generated, which may decrease characteristics such as toughness. For this reason, the Ti content is set to 0.050 mass% or less. It is preferably 0.040 mass% or less, more preferably 0.030 mass% or less, even more preferably 0.020 mass% or less, and even more preferably 0.015 mass% or less.

[0030] (N:0.0010~0.0100% by mass) N has the effect of forming nitrides with Al and the like to refine the structure and improve the toughness of the base material and the welded heat affected zone, so in order to realize this effect, the N content is set to 0.0010 mass% or more. It is preferably 0.0020 mass% or more, more preferably 0.0030 mass% or more, and even more preferably 0.0040 mass% or more. However, if the N content is excessive, the amount of nitrides precipitated in the base material increases, the base material toughness is significantly reduced, and even in the welded heat affected zone, coarse carbonitrides are formed, reducing the toughness. Therefore, the N content is set to 0.0100 mass% or less. It is preferably 0.0080 mass% or less, more preferably 0.0070 mass% or less, and even more preferably 0.0060 mass% or less.

[0031] (The total content of Si and Cu is 0.30 mass% or more) Si and Cu have a common function of suppressing the proliferation of dislocations, thereby extending the crack initiation life and improving the fatigue limit ratio. This function can be more effectively exerted when the total content of Si and Cu ([Si]+[Cu]) is 0.30 mass% or more. It is preferably 0.40 mass% or more, more preferably 0.50 mass% or more, and even more preferably 0.60 mass% or more. The preferred upper limit of [Si]+[Cu] is the sum of the respective preferred upper limits.

[0032] The thick steel plate according to the embodiment of the present invention preferably contains the above-mentioned composition, and in one embodiment of the present invention, the balance is preferably iron and inevitable impurities. As inevitable impurities, the inclusion of elements brought in due to the conditions of raw materials, materials, manufacturing facilities, etc. is permitted. Note that, for example, there are elements such as P and S, which are usually preferable to have a lower content and are therefore inevitable impurities, but whose composition ranges are separately specified as above. For this reason, in this specification, when the term "unavoidable impurities" is used, it is a concept excluding elements whose composition ranges are separately specified.

[0033] Furthermore, the steel plate according to the embodiment of the present invention may selectively contain the following optional elements as necessary, and the properties of the steel are further improved depending on the components contained therein.

[0034] (one or more selected from the group consisting of Ni: more than 0 mass% and not more than 1.00 mass%, Ca: more than 0 mass% and not more than 0.0050 mass%, B: more than 0.0003 mass% and not more than 0.0050 mass%, V: 0.003 to 0.500 mass%, Cr: 0.05 to 1.00 mass%, and Mo: 0.010 mass% or more and less than 0.05 mass%) Ni has the effect of improving hardenability and refining the structure, and at the same time, has the effect of suppressing cracking during hot working, which is easily caused by the addition of Cu. In order to exert such effects, the Ni content is preferably more than 0 mass%. More preferably, it is 0.10 mass% or more, and further preferably, it is 0.20 mass% or more. However, if the Ni content is excessive, the hardenability becomes excessive, and the MA fraction becomes excessive, and the desired fatigue properties cannot be obtained. Therefore, the Ni content is set to 1.00 mass% or less. It is preferably 0.80 mass% or less, more preferably 0.60 mass% or less, and further preferably 0.40 mass% or less.

[0035] Ca is an element useful for controlling the shape of sulfide-based inclusions, and in order to exert this effect, the Ca content is preferably more than 0 mass%. More preferably, it is 0.0005 mass% or more, even more preferably, it is 0.0008 mass% or more, and even more preferably, it is 0.0010 mass% or more. However, if the Ca content is excessive, it leads to a decrease in cleanliness and a deterioration in toughness. Therefore, the Ca content is set to 0.0050 mass% or less, preferably 0.0040 mass% or less, more preferably 0.0035 mass% or less, and even more preferably 0.0030 mass% or less.

[0036] B is an element that improves hardenability, and in particular, it is an element that inhibits the formation of coarse ferrite structures and makes it easier to form fine upper bainite structures. In order to achieve this effect, the B content is preferably more than 0.0003 mass%, more preferably 0.0005 mass% or more, and even more preferably 0.0010 mass% or more. However, if the B content is excessive, the hardenability becomes excessive, and the MA fraction becomes excessive, making it impossible to obtain the desired fatigue properties, so the B content is set to 0.0050 mass% or less, and preferably 0.0040 mass% or less.

[0037] V, Cr, and Mo are elements that have the effect of improving the hardenability of steel sheets and are effective in refining the structure. In order to exert such an effect, it is preferable to contain one or more of V: ​​0.003 mass% or more, Cr: 0.05 mass% or more, and Mo: 0.010 mass% or more. However, if these elements are contained in excess, the hardenability becomes excessive, the MA fraction becomes excessive, and the desired fatigue properties cannot be obtained. Therefore, the respective amounts are set to V: 0.500 mass% or less, Cr: 1.00 mass% or less, and Mo: less than 0.05 mass%. Preferably, V: 0.400 mass% or less, Cr: 0.80 mass% or less, and Mo: 0.04 mass% or less. More preferably, V: 0.300 mass% or less, Cr: 0.60 mass% or less, and Mo: 0.03 mass% or less. More preferably, V is 0.200 mass % or less, Cr is 0.40 mass % or less, and Mo is 0.02 mass % or less.

[0038] In addition, Ni, Ca, B, V, Cr and Mo may each be contained alone or in combination of two or more kinds. When two or more kinds are contained, at least one of them may be contained in any content within the above-mentioned range, and the others may be contained in any content within a range not exceeding the above-mentioned upper limit.

[0039] (one or more selected from the group consisting of REM: more than 0 mass% and not more than 0.0060 mass%, Zr: more than 0 mass% and not more than 0.0050 mass%, Mg: 0.0005 to 0.0100 mass%, and Ta: 0.010 to 0.500 mass%) REM includes lanthanoid elements (15 elements from La to Lu), Sc (scandium) and Y (yttrium). REM is a deoxidizing element, and in order to exert its effect, the REM content is preferably more than 0 mass%, more preferably 0.0010 mass% or more, and even more preferably 0.0015 mass% or more. On the other hand, if the REM content is excessive, coarse oxides are formed, and the balance between strength and toughness is deteriorated. Therefore, the REM content is set to 0.0060 mass% or less. It is preferably 0.0050 mass% or less, and more preferably 0.0045 mass% or less.

[0040] Zr is also a deoxidizing element, and in order to exert its effect, the Zr content is preferably more than 0 mass%, more preferably 0.0010 mass% or more, and even more preferably 0.0012 mass% or more. On the other hand, if the Zr content is excessive, coarse oxides are formed, and the balance between strength and toughness deteriorates. Therefore, the Zr content is set to 0.0050 mass% or less, preferably 0.0045 mass% or less, and more preferably 0.0040 mass% or less.

[0041] Mg is an element that forms stable oxides at high temperatures, effectively suppresses the coarsening of prior austenite (γ) grains in the heat-affected zone, and is effective in improving the toughness of the weld. Therefore, the Mg content is preferably 0.0005% by mass or more, and more preferably 0.0010% by mass or more. However, if the Mg content is excessive, the amount of inclusions increases and the toughness decreases. Therefore, the Mg content is set to 0.0100% by mass or less, and preferably 0.0050% by mass or less.

[0042] Ta is effective in improving strength, and in order to exert this effect, the Ta content is preferably 0.010 mass% or more, more preferably 0.030 mass% or more. However, if the Ta content is excessive, the toughness decreases due to the formation of precipitates. Therefore, the Ta content is set to 0.500 mass% or less, preferably 0.200 mass% or less, more preferably 0.150 mass% or less.

[0043] In addition, REM, Zr, Mg, and Ta may each be contained alone or in combination of two or more kinds. When two or more kinds are contained, at least one of them may be contained in an arbitrary content within the above-mentioned range, and the others may be contained in an arbitrary content within a range not exceeding the above-mentioned upper limit.

[0044] <2.Metal structure> The steel plate according to the embodiment of the present invention has an MA fraction of 0.5 area % or less, and the total length of low-angle grain boundaries observed in a 200 μm square region (hereinafter simply referred to as "total length of low-angle grain boundaries") is 2.5 mm or more. Each of these will be described in detail below.

[0045] (MA fraction is 0.5 area % or less) MA is a martensite-austenite mixed phase, also known as island martensite. MA is very harmful to improving the fatigue limit ratio, and even an MA fraction exceeding 0.5 area % can significantly reduce the fatigue limit ratio. Therefore, the MA fraction is set to 0.5 area % or less. It is preferably 0.3 area % or less, more preferably 0.2 area % or less, even more preferably 0.1 area % or less, and most preferably 0 area %.

[0046] Other metal structures are not particularly limited, but the total fraction of ferrite and pearlite (including pseudo-pearlite) is preferably 80 area % or more of the total. More preferably, it is 90 area % or more, and most preferably, it is 100 area %. Furthermore, it is preferable that the ferrite fraction is higher than the pearlite fraction in order to increase the elongation and / or toughness during tensile testing. Furthermore, when the metal structure contains bainite or martensite, it is preferable that the MA fraction is 0.5 area % or less, and the total fraction of bainite, martensite and MA is 20 area % or less. This can suppress the increase in mobile dislocations in the parent phase and suppress the deterioration of fatigue properties. More preferably, it is 10 area % or less.

[0047] The MA fraction can be determined, for example, by observing an arbitrary surface at a depth of 2 mm or more from the surface of the thick steel plate in the thickness direction and within 1 / 4 of the plate thickness in a cross section parallel to the rolling direction of the thick steel plate and perpendicular to the surface of the thick steel plate. The reason for the "depth of 2 mm or more" is that a scale layer of about 0.1 to 2 mm exists on the surface of the thick steel plate after hot rolling depending on the manufacturing conditions, and the part excluding this is evaluated. The reason for the "within 1 / 4 of the plate thickness" is that fatigue cracks can occur from the surface of the steel plate, and therefore the metal structure inside the steel plate may not provide results that sufficiently correspond to the fatigue properties.

[0048] In the embodiment of the present invention, although not particularly limited, the MA fraction can be reduced to 0.5 area % or less by, for example, the method described below. In the embodiment of the present invention, a relatively large amount of Si is contained in order to improve the fatigue limit ratio. On the other hand, in a steel plate having a high Si content, MA is easily generated. In order to make the MA fraction of a steel plate having a high Si content 0.5 area % or less, the inventors focused on hardenability, which is correlated with martensite formation, and in particular, on DI, which is represented by the well-known formula (3) below. DI = 1.16 × ([C] / 10) 0.5 ×(0.7×[Si]+1)×(5.1×([Mn]-1.2)+5)×(0.35×[Cu]+1)×(0.36×[Ni]+1)×(2.16×[Cr]+1)×(3×[Mo]+1)×(1.75×[V]+1)×(200×[B]+1) ···(3) In the above formula (3), [C], [Si], [Mn], [Cu], [Ni], [Cr], [Mo], [V] and [B] respectively represent the contents of C, Si, Mn, Cu, Ni, Cr, Mo, V and B expressed in mass%. The DI is an index of the hardenability of steel, and is the maximum diameter (inches) at which a round bar test piece transforms into martensite up to the center, and is affected by the type and / or amount of added elements. In other words, the lower the DI, the less likely martensite is to form. In the thick steel plate according to the embodiment of the present invention, ferrite and pearlite may be the main components (parent phase structure), but in the cooling process, alloy elements such as carbon may become concentrated in the remaining structure other than the parent phase structure, and MA may form. The inventors came up with the idea of ​​controlling the ease of formation of this MA using the same concept as the DI value.

[0049] The present inventors have improved the above formula (3) as follows to suit the actual conditions of the steel plate according to the embodiment of the present invention. First, in a steel plate having the composition (or a composition close thereto) of the embodiment of the present invention, MA is generated in the remaining structure after transformation from austenite to ferrite-pearlite, and carbon is strongly concentrated at that time, so [C] is fixed at 0.77 mass% of the eutectoid composition. Furthermore, since B is easily precipitated as BN, etc., the effective amount of dissolved B that is generated is [B *] was substituted into [B] in the above formula (3). [B * ]=[B]-(([N]-[Ti]×14 / 48)×11 / 14) ···(2) In the above formula (2), [B], [N] and [Ti] respectively represent the contents of B, N and Ti expressed in mass %. However, in controlled rolling, [B * It is known that the hardenability is affected only when [B * ] is 4 x 10 -4 It has been found that the hardenability is affected at mass% or more. * ]<4×10 -4 (mass%), [B * ]=0 (mass %).

[0050] As a result of the above improvement, the above formula (3) becomes the following formula (1). Note that after the improvement, "DI" has been changed to "DI2". DI2 = 1.16 × (0.77 / 10) 0.5 ×(0.7×[Si]+1)×(5.1×([Mn]-1.2)+5)×(0.35×[Cu]+1)×(0.36×[Ni]+1)×(2.16×[Cr]+1)×(3×[Mo]+1)×(1.75×[V]+1)×(400×[B * ]+1) ···(1) In the above formula (1), [Si], [Mn], [Cu], [Ni], [Cr], [Mo] and [V] respectively represent the contents of Si, Mn, Cu, Ni, Cr, Mo and V in mass%, and [B * ] is the amount of dissolved B effectively produced, as expressed by the above formula (2).

[0051] The present inventors have found that by controlling the cooling method after hot rolling (described later) to make the hardenability index DI2 3.90 or less, the MA fraction can be made 0.5 area % or less, preferably 3.85 or less, more preferably 3.80 or less, even more preferably 3.70 or less, and most preferably 3.60 or less.

[0052] In order to keep the MA fraction at 0.5% by area or less, it is necessary to control the cooling method after hot rolling. Specifically, after hot rolling, the average cooling rate to room temperature is set to 3°C / sec or less, for example by air cooling. The average cooling rate is preferably 2°C / sec or less, and more preferably 1°C / sec or less. If the average cooling rate to room temperature is faster than 3°C / sec, for example by water cooling, a large amount of MA will be generated. The average cooling rate is calculated based on the temperature of the steel plate surface.

[0053] (Total length of low-angle grain boundaries is 2.5 mm or more) The inventors have found that while low-angle grain boundaries are unlikely to hinder dislocation motion under high stress such as tensile strength, they greatly hinder dislocation motion under low stress such as repeated stress in fatigue. In other words, the fatigue limit ratio can be greatly improved by having many low-angle grain boundaries. The present inventors have found that a steel plate having a sufficiently high fatigue limit ratio can be provided by adjusting the composition to a predetermined composition as described above in <1. Composition>, setting the MA fraction to 0.5 area % or less, and setting the total length of low-angle grain boundaries to 2.5 mm or more. The total length is preferably 3.0 mm or more, more preferably 3.4 mm or more, and even more preferably 5.0 mm or more. The longer the total length of low-angle grain boundaries, the better, and there is no particular upper limit.

[0054] In order to obtain the desired total length of low angle grain boundaries in the steel plate according to the embodiment of the present invention, hot rolling is performed in a temperature range including at least the two-phase temperature range from the Ar1 transformation point to less than the Ar3 transformation point, and the reduction in the two-phase temperature range is set to 10% or more, preferably 15% or more, more preferably 18% or more, even more preferably 19% or more, and most preferably 20% or more. There is no particular upper limit to the reduction in the two-phase temperature range, but from the viewpoint of productivity, it is preferably performed at 60% or less. The Ar1 transformation point can be determined from the volume change of a test piece accompanying a temperature drop using a hot working reproduction test or the like, and can be approximately 600°C in the case of the thick steel plate according to the embodiment of the present invention. In an embodiment of the present invention, the Ar3 transformation point is calculated by the following formula (4). Ar3(℃)=910-310[C]-80[Mn]-20[Cu]-15[Cr]-55[Ni]-80[Mo]+0.35(t-8)...(4) In the above formula (4), [C], [Mn], [Cu], [Cr], [Ni] and [Mo] represent the contents of C, Mn, Cu, Cr, Ni and Mo, respectively, expressed in mass%, and t represents the plate thickness (mm).

[0055] The total length of low-angle grain boundaries can be determined, for example, by analyzing an arbitrary surface located at a depth of 2 mm or more from the surface of the thick steel plate in the thickness direction and within 1 / 4 of the thickness in a cross section parallel to the rolling direction of the thick steel plate and perpendicular to the surface of the thick steel plate by SEM-EBSD. The reason for the "depth of 2 mm or more" is that a scale layer of about 0.1 to 2 mm exists on the surface of the thick steel plate after hot rolling depending on the manufacturing conditions, and the part excluding this is evaluated. The reason for the "within 1 / 4 of the thickness" is that fatigue cracks can occur from the surface of the steel plate, and therefore the metal structure inside the steel plate may not provide results that sufficiently correspond to the fatigue properties.

[0056] The thickness of the steel plate according to the embodiment of the present invention is not particularly limited, but is preferably 6 mm or more since the effect of improving fatigue properties is significant, more preferably 9 mm or more, and further preferably 12 mm or more.

[0057] The steel plate according to the embodiment of the present invention is not particularly limited in tensile strength or yield strength as long as the desired metal structure is obtained. For example, when used as a structural material for a ship's hull, the tensile strength and yield strength may be controlled according to the ship classification standard. For example, the tensile strength of the YP32 class of Nippon Kaiji Kyokai is 440 to 590 MPa, and that of the YP36 class is 490 to 620 MPa.

[0058] <3. Manufacturing method> A method for producing a steel plate according to an embodiment of the present invention includes the steps of: preparing a steel slab having the composition described above in <1. Composition>; (a) hot rolling the steel slab in a two-phase temperature range with a rolling reduction of 10% or more; and (b) cooling the steel slab to room temperature at an average cooling rate of 3°C / sec or less after the hot rolling in the two-phase temperature range. In the composition of the steel slab, it is preferable that DI2 represented by the above formula (1) is set to 3.90 or less. Each step will be described in detail below. The above-mentioned steel billets can be produced by a general steelmaking method. The heating temperature and average cooling rate during hot rolling are based on the surface temperature of the steel plate (or billet).

[0059] (a) Hot rolling process Hot rolling is performed in a temperature range including at least the two-phase temperature range from the Ar1 transformation point to less than the Ar3 transformation point, and the rolling reduction in the two-phase temperature range is 10% or more. It is preferably 15% or more, more preferably 18% or more, even more preferably 19% or more, and most preferably 20% or more. There is no particular upper limit to the rolling reduction in the two-phase temperature range, but it is preferably 60% or less from the viewpoint of productivity. In addition, hot rolling in the two-phase temperature range is preferably started in the range of Ar3-10°C to Ar3-80°C and finished at Ar3-20°C to Ar3-100°C. This allows the total length of the low-angle grain boundaries to be longer. The reduction ratio in the two-phase temperature region is calculated by the following formula (5). Reduction rate in the two-phase temperature range (%) = (t1-t2) / t1 × 100 (5) Here, t1 is the plate thickness (mm) of the steel billet (slab, etc.) before hot rolling, and t2 is the plate thickness (mm) of the steel plate after hot rolling in the two-phase temperature range.

[0060] Before hot rolling, the steel slab is preferably heated to a temperature range of 1000 to 1250°C. More preferably, the temperature is 1050°C or higher. It is preferable to heat the slab to a temperature range of 1000°C or higher, which is sufficiently higher than the Ar3 transformation point, while preventing the crystal grains from becoming coarse. However, if the heating temperature becomes too high and exceeds 1250°C, the structure size cannot be reduced even if sufficient rolling reduction is applied, so the temperature is preferably 1250°C or lower. More preferably, the temperature is 1200°C or lower, and even more preferably, the temperature is 1150°C or lower.

[0061] It is preferable to perform hot rolling in the non-recrystallized region at or above the Ar3 transformation point before hot rolling in the two-phase temperature region. This allows the average grain size of the resulting steel plate to be small. The rolling reduction in the non-recrystallized region is preferably 10% or more, more preferably 20% or more, and even more preferably 30% or more. This allows the average grain size of the resulting steel plate to be small. The upper limit temperature at which the non-recrystallized region is reached can be evaluated by a hot working reproduction test or the like, and can be approximately 900°C in the steel plate according to the embodiment of the present invention. When hot rolling in the non-recrystallized region is performed in addition to hot rolling in the two-phase temperature region, the reduction in the non-recrystallized region is calculated by the following formula (6), and the reduction in the two-phase temperature region is calculated by the following formula (7) instead of the above formula (5). Reduction rate in unrecrystallized region (%) = (t1-t3) / t1 × 100 (6) Reduction rate in the two-phase temperature range (%) =(t1-t2) / t1×100-(t1-t3) / t1×100 =(t3-t2) / t1×100 (7) Here, t1 is the thickness (mm) of the steel billet (slab, etc.) before hot rolling, t2 is the thickness (mm) of the steel plate after hot rolling in the two-phase temperature region, and t3 is the thickness (mm) of the steel plate after hot rolling in the non-recrystallized region.

[0062] Before the above-mentioned hot rolling in the two-phase temperature range and hot rolling in the non-recrystallized range, hot rolling in the recrystallized range at a temperature equal to or higher than the non-recrystallized range may be performed. When hot rolling in the recrystallized region is performed in addition to hot rolling in the two-phase temperature region and hot rolling in the non-recrystallized region, the reduction in the recrystallized region is calculated as shown in the following formula (8), the reduction in the non-recrystallized region is calculated as shown in the following formula (9) instead of the above formula (6), and the reduction in the two-phase temperature region is calculated as shown in the following formula (10) (i.e., the same as the above formula (7)) instead of the above formula (5). Reduction rate in the recrystallized region (%) = (t1-t4) / t1 × 100 (8) Reduction rate in unrecrystallized region (%) =(t1-t3) / t1×100-(t1-t4) / t1×100 =(t4-t3) / t1×100 (9) Reduction rate in the two-phase temperature range (%) =(t1-t2) / t1×100-(t1-t4) / t1×100-(t4-t3) / t1×100 =(t3-t2) / t1×100 (10) Here, t1 is the thickness (mm) of the steel billet (slab, etc.) before hot rolling, t2 is the thickness (mm) of the thick steel plate after hot rolling in the two-phase temperature region, t3 is the thickness (mm) of the thick steel plate after hot rolling in the non-recrystallized region, and t4 is the thickness (mm) of the thick steel plate after hot rolling in the recrystallized region.

[0063] (b) Cooling process After hot rolling in the two-phase temperature range, the steel is cooled to room temperature at an average cooling rate of 3°C / sec or less. For example, cooling by air cooling is considered. This makes it possible to reduce the MA fraction. The average cooling rate is preferably 2°C / sec or less, more preferably 1°C / sec or less.

[0064] Within the scope of achieving the object of the embodiment of the present invention, the method for manufacturing a steel plate according to the embodiment of the present invention may include other steps. EXAMPLES

[0065] The following examples are provided to more specifically describe the embodiments of the present invention. The embodiments of the present invention are not limited to the following examples, and may be modified as appropriate within the scope of the above and below-described aims, and all of these are included in the technical scope of the embodiments of the present invention.

[0066] Steel billets (slabs of 255 mm square) A to J having the composition shown in Table 1 were melted in a 250-ton converter of an actual machine (manufacturing machine). Then, in a rolling line of the actual machine having a rolling pass for hot rolling in the non-recrystallized region and a rolling pass for hot rolling in the two-phase temperature region, the steel plates of Examples 1 to 6 and Comparative Examples 1 to 8 were produced under the conditions of Table 2 described later. The hot rolling in the non-recrystallized region was performed in a temperature range of the Ar3 transformation point or higher and lower than 900°C. After the hot rolling in the two-phase temperature region, all cooling to room temperature was performed by air cooling, with an average cooling rate of 1°C / s or less. In the examples and comparative examples, evaluations were performed by hot working reproduction tests, and as a result, the upper limit temperature of the unrecrystallized region was about 900°C, and the Ar1 transformation point was about 600°C.

[0067] [Table 1]

[0068] [Table 2]

[0069] [Evaluation of MA fraction] A sample was taken from a position 3 to 4 mm from the surface of the thick steel plate. A surface 3 to 4 mm from the surface of the thick steel plate in the thickness direction in a cross section parallel to the rolling direction of the thick steel plate and perpendicular to the surface of the thick steel plate was mirror-polished, and then etched using a Lepera etching solution made by mixing liquid A (a solution of 3 g picric acid and 100 ml ethanol), liquid B (a solution of 1 g sodium disulfite and 100 ml distilled water), and ethanol in a ratio of (liquid A:liquid B:ethanol) = (5:6:1). The etched surface was then examined with an observation area of ​​3.71 x 10 -2 mm 2 Two points were observed at a magnification of 400x, and the structures were classified and the relationship between the ratios of each structure was investigated. The white corroded phase was then considered to be MA, and the MA ratio was calculated using image analysis software (Image Pro ver.7.0.1), and the average value of the MA ratios at the two points was used.

[0070] [Evaluation of the total length of low-angle grain boundaries and average grain size] The total length of low-angle grain boundaries and the average grain size were measured by SEM-EBSD on the surface located 2.9 to 3.1 mm from the surface of the steel plate in the thickness direction in a cross section parallel to the rolling direction of the steel plate and perpendicular to the surface of the steel plate. Specifically, the total length of low-angle grain boundaries and the average grain size of the surface were obtained by combining an EBSD device ("OIM" manufactured by TEX SEM Laboratries) with an SEM ("IT-100" manufactured by JEOL). The analysis was performed using the analysis software OIM Analysis (Ver. 7.3.1), and the total length of low-angle grain boundaries and the average grain size were obtained by the area fraction method, with the area surrounded by high-angle grain boundaries with an orientation difference of 15° or more between adjacent grains being considered as grains. The measurement conditions were a measurement area of ​​200 μm × 200 μm, a measurement step of 0.4 μm intervals, and measurement points with a confidence index (CI) of less than 0.1, which indicates the reliability of the measurement orientation, were excluded from the analysis. For crystal grains and low-angle grain boundaries that were partially contained in the measurement region, analysis was performed only on the portions that were contained in the measurement region.

[0071] [Fatigue limit ratio evaluation] Tensile test pieces (plate thickness 4 mm, gauge length 35 mm) having the shape shown in FIG. 1 were taken from a position 2 to 6 mm deep from the surface of each thick steel plate such that the longitudinal direction of the tensile test piece (i.e., the load direction of the tensile test) was perpendicular to the rolling direction and plate thickness direction of the thick steel plate, and tensile strength TS and yield strength YS were measured by conducting a tensile test in accordance with JIS Z2241:2011. In addition, 4 mm thick steel plate samples were cut out from a position 2 to 6 mm deep from the surface of each thick steel plate, and fatigue test pieces having the shapes shown in Fig. 2A (top view) and Fig. 2B (side view) were prepared so that the longitudinal direction of the fatigue test piece (i.e., the load direction of the fatigue test) was perpendicular to the rolling direction and plate thickness direction of the thick steel plate, and fatigue tests were performed on these pieces. Specifically, the surfaces of the fatigue test pieces were polished with emery paper up to #1200 to remove the effects of the surface condition, and then fatigue tests were performed under the following conditions using an Instron electrohydraulic servo fatigue tester. Test environment: Room temperature, in air Control method: Load control Control waveform: Sine wave Stress ratio: R=-1 Test speed: 20Hz Test cycle count: 5 million without breakage

[0072] In the fatigue test, the applied stress is σ a (MPa) and tensile strength is TS (MPa), σ a The test was performed at an arbitrary stress amplitude where / TS = 0.65 to 0.7, and if a fracture occurred, the stress amplitude was lowered by 20 MPa at a time and the test was repeated until no fracture occurred. The test was then performed by increasing the stress amplitude by 10 MPa from the stress amplitude at which no fracture occurred, and the median between the minimum stress amplitude at which fracture occurred and the maximum stress amplitude at which no fracture occurred was taken as the fatigue limit σw (MPa). The fatigue limit ratio (σw / TS) was calculated from the obtained fatigue limit and tensile strength. The fatigue limit ratio was judged to be sufficiently high (◯) when the fatigue limit ratio was rounded off to three decimal places and was 0.60 or more, and was judged to be insufficient (×) when it was less than 0.60. The results are shown in Table 3. In the columns of "Structure Classification" and "Relative Fraction of Each Structure" in Table 3, "F" indicates ferrite, "P" indicates pearlite, "B" indicates bainite, and "MA" indicates a mixed phase of martensite and austenite.

[0073] [Table 3]

[0074] The results in Table 3 can be considered as follows: All of Examples 1 to 6 in Table 3 are examples that satisfy all of the requirements stipulated in the embodiments of the present invention, and had sufficiently high fatigue limit ratios and excellent fatigue characteristics. On the other hand, Comparative Examples 1 to 8 are examples that do not satisfy the requirements defined in the embodiment of the present invention, and the fatigue limit ratios were insufficient.

[0075] In Comparative Examples 1 and 4, the rolling reduction in the two-phase temperature region was less than 10%, so the total length of the low-angle grain boundaries was less than 2.5 mm, resulting in an insufficient fatigue limit ratio.

[0076] In Comparative Examples 2, 3 and 8, the rolling reduction in the two-phase temperature region was less than 10%, so the total length of the low-angle grain boundaries was less than 2.5 mm, and the DI2 was more than 3.90, so the MA fraction exceeded 0.5 area %, resulting in an insufficient fatigue limit ratio.

[0077] Comparative Examples 5 and 7 did not satisfy the component composition defined in the embodiment of the present invention. In particular, the Cu content was less than 0.10 mass% and the total content of Si and Cu was less than 0.30 mass%, resulting in an insufficient fatigue limit ratio.

[0078] In Comparative Example 6, the reduction ratio in the two-phase temperature region was less than 10%, so the total length of the low-angle grain boundaries was less than 2.5 mm, and the composition did not satisfy the composition defined in the embodiment of the present invention. In particular, the Cu content was less than 0.10 mass% and the total content of Si and Cu was less than 0.30 mass%, so the fatigue limit ratio was insufficient.

[0079] The relationship between DI2 and the MA fraction will be explained more specifically below with reference to a reference example. Steel billets (inserts) a to j having the composition shown in Table 4 were produced by VIF melting, cut into plates having a thickness of 120 mm, and then hot rolled under the conditions shown in Table 5 to produce the thick steel plates of Reference Examples 1 to 10. The MA fractions of Reference Examples 1 to 10 were evaluated in the same manner as in the Examples. The results are shown in Table 5. In all Reference Examples, the hot rolling was hot rolling in the unrecrystallized region, and the rolling reduction was calculated according to the above formula (6).

[0080] [Table 4]

[0081] [Table 5]

[0082] The results in Table 5 can be considered as follows: Reference Example 8 in Table 5 is an example in which DI2 was 3.90 or less, and the MA fraction was 0.5 area % or less. On the other hand, in Reference Examples 1 to 7 and 9, the MA fraction exceeded 0.5 area % because DI2 exceeded 3.90, etc. In Reference Example 10, DI2 was 3.90 or less, but the Mo content was 0.05 mass % or more, so the MA fraction exceeded 0.5 area %.

[0083] The following examples further illustrate the embodiments of the present invention in more detail. Steel slabs (inserts) K having the composition shown in Table 6 were produced by VIF melting, cut into plates with a thickness of 150 mm, and then hot-rolled under the conditions shown in Table 7 to produce the steel plates of Examples 7 and 8. The hot rolling in the non-recrystallized region was performed in a temperature range from the Ar3 transformation point to less than 900° C. After the hot rolling in the two-phase temperature range, cooling to room temperature was all performed by air cooling, with an average cooling rate of 1° C. / s or less. In Examples 7 and 8, evaluation by a hot working reproduction test revealed that the upper limit temperature of the non-recrystallized region was about 900°C, and the Ar1 transformation point was about 600°C.

[0084] [Table 6]

[0085] [Table 7]

[0086] The thick steel plates of Examples 7 to 8 were evaluated in the same manner as in Examples 1 to 6 and Comparative Examples 1 to 8. The results are shown in Table 8. Note that, for the fatigue test of the thick steel plate of Example 8, a fatigue test specimen having the shape shown in Fig. 3A (top view) and Fig. 3B (side view) was prepared so that the longitudinal direction of the fatigue test specimen (i.e., the load direction in the fatigue test) was perpendicular to the rolling direction and plate thickness direction of the thick steel plate, and then the fatigue test was performed.

[0087] [Table 8]

[0088] The results in Table 8 can be considered as follows: Examples 7 to 8 in Table 8 are all examples that satisfy all of the requirements stipulated in the embodiment of the present invention, and had sufficiently high fatigue limit ratios and excellent fatigue properties. [Industrial Applicability]

[0089] The thick steel plate according to the embodiment of the present invention has a sufficiently high fatigue limit ratio and excellent fatigue properties, and is therefore suitable as a structural material for ships, buildings, bridges, construction machinery, and the like.

Claims

1. The composition of the components is C: 0.02 to 0.10% by mass, Si: 0.10 to 0.60% by mass, Mn: 1.00 to 2.00% by mass, P: more than 0% by mass and not more than 0.035% by mass, S: more than 0% by mass and not more than 0.035% by mass, Cu: 0.10 to 0.60% by mass, Al: 0.010 to 0.060% by mass, Nb: more than 0% by mass and not more than 0.050% by mass, Ti: more than 0% by mass and not more than 0.050% by mass, N: 0.0010 to 0.0100 mass%, and The balance is composed of iron and inevitable impurities, and The total content of Si and Cu is 0.30 mass% or more, The metal structure is The MA fraction is 0.5 area% or less, and The total length of low-angle grain boundaries observed in a 200 μm square area is 2.5 mm or more. Here, the low-angle grain boundary refers to a boundary where the difference in orientation between adjacent crystal grains is 2 to 15 degrees.

2. Ni: more than 0% by mass and not more than 1.00% by mass, Ca: more than 0% by mass and not more than 0.0050% by mass, B: more than 0.0003% by mass and not more than 0.0050% by mass, V: 0.003 to 0.500% by mass, Cr: 0.05 to 1.00 mass%; and The steel plate according to claim 1 , further comprising at least one element selected from the group consisting of Mo: 0.010 mass % or more and less than 0.05 mass %.

3. REM: more than 0% by mass and not more than 0.0060% by mass, Zr: more than 0% by mass and not more than 0.0050% by mass, Mg: 0.0005 to 0.0100% by mass, and The steel plate according to claim 1 or 2, further comprising one or more elements selected from the group consisting of Ta: 0.010 to 0.500 mass%.

4. The steel plate according to any one of claims 1 to 3, wherein a hardenability index DI2 represented by the following formula (1) is 3.90 or less. DI2=1.16×(0.77 / 10) 0.5 ×(0.7×[Si]+1)×(5.1×([M]-+1.2)+5)×(0.35×[[]+1)×(0.36×[Ni]+1)×(2.16×[[]+1)×(3×[[]++1)×(1.75×[V]++1)×(400×[[ * ]+1) ・・・(1) In the formula (1), [Si], [Mn], [Cu], [Ni], [Cr], [Mo] and [V] respectively represent the contents of Si, Mn, Cu, Ni, Cr, Mo and V in mass%, and [B * is the amount of dissolved B effectively produced, as expressed by the following formula (2). [B * ]=[B]-(([N]-[T]]×14 / 48)×11 / 14) ・・・(2) In formula (2), [B], [N] and [Ti] respectively represent the contents of B, N and Ti expressed in mass %. * ]<4×10 -4 In the case of (mass%), [B * ] is regarded as 0 (mass %).

5. A step of preparing a steel slab having a composition according to any one of claims 1 to 4; hot rolling the slab at a rolling reduction of 10% or more in a two-phase temperature range; The method for producing a steel plate according to any one of claims 1 to 4, further comprising: a step of cooling to room temperature at an average cooling rate of 3 ° C. / sec or less after the step of hot rolling in the two-phase temperature range.

6. After the step of preparing the steel billet, and before the step of hot rolling in the two-phase temperature range, a step of heating the steel billet to 1000 to 1250°C; The method according to claim 5, further comprising the step of hot rolling in a non-recrystallized region with a rolling reduction of 10% or more after the heating step.

Citation Information

Patent Citations

  • High-strength thick steel plate superior in drop-weight properties and toughness of base metal

    JP2011047032A

  • HIGH STRENGTH STEEL SHEET EXCELLENT IN HYDROGEN EMBRITTLEMENT RESISTANCE AND HAVING THE MAXIMUM TENSILE STRENGTH OF &gt;=900 MPa, METHOD FOR PRODUCING HIGH STRENGTH COLD ROLLED STEEL SHEET, AND METHOD FOR PRODUCING HIGH STRENGTH GALVANIZED STEEL SHEET

    JP2011111675A

  • Thick steel plate for ultra-low temperature and method for producing the same

    JP2011219848A

  • High strength hot rolled steel sheet for line pipe excellent in on-site weldability and method for producing the same

    JP2013147694A

  • Steel sheet

    JP2015098642A